Line Balancing Optimization in Shoe Finishing Production Systems: Optimasi Keseimbangan Jalur dalam Sistem Produksi Penyelesaian Sepatu - Cahyaningurm, Rista Dwi; Sukmono, Tedjo (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Manufacturing systems often face inefficiencies due to unbalanced workloads across workstations, particularly in labor-intensive industries such as shoe production. Specific Background: In the finishing process of a shoe manufacturing company, production targets were not achieved due to bottlenecks in the creaming brushing process, where operation time exceeded the cycle time of 1.215 minutes. Knowledge Gap: Previous applications of line balancing methods have not sufficiently addressed workload imbalance in finishing lines with complex task distributions. Aims: This study aims to optimize the production line by applying the Largest Candidate Rule (LCR) and Region Approach (RA) methods to improve efficiency and workload distribution. Results: The findings show that both methods significantly improve performance, increasing line efficiency to 81.73%, reducing balance delay to 18.27%, and decreasing idle time to 1.998 minutes, while reducing the number of workstations from 15 to 9. Novelty: The study provides a comparative application of LCR and RA methods within a real shoe production finishing line and identifies layout considerations as a determining factor in method selection. Implications: The results suggest that implementing appropriate line balancing methods can support production target achievement and improve operational efficiency in manufacturing systems. Keywords: Line Balancing, Production Systems, Largest Candidate Rule, Region Approach, Workstation Optimization Key Findings Highlights Workstation reduction achieved through task redistribution across production stages Idle time minimized alongside improved workload allocation consistency Layout-based selection supports practical implementation of balancing methods